Efeitos do envelhecimento na mucosa intestinal: indução e declínio da tolerância oral - Andrezza Fernanda Santiago (2011)
Aging is reported to be associated with a decline in oral tolerance induction, an immunological phenomenon initiated at the intestinal mucosal surface. Mice become less susceptible with 24 weeks of age and totally refractory with 70 weeks of age. At this age, they can still be rendered tolerant but only by a regimen of continuous feeding. Herein, we examined the effect of aging in T cells and cytokines at the intestinal mucosa that are described as involved in oral tolerance induction. Frequencies of regulatory-type IEL subsets TCRgd+ and CD8aa are lower in 24-month-old-mice. Production of TGF-b and IL-10 in the small intestine was also reduced during aging. However, mucosal CD4+CD25+Foxp3+ and CD4+LAP+ regulatory T cells increased in mice from 6 months of age. Activated CD4+CD44+ mucosal T cells also augmented. Moreover, the expression of costimulatory molecule CD86 in DCs was augmented and the ability of mucosal dendritic cells to stimulate TGF-b secretion and differentiation of CD4+LAP+ T cells in co-culture studies also declined in 12-month-old-mice. Reduction in these regulatory-type cytokines and T cells may help to explain the decline in susceptibility to oral induction during aging. However, not all mucosal regulatory elements are diminished; CD4+CD25+Foxp3+ as well as CD4+CD25+LAP+ regulatory T cells are augmented and they might play a critical role in maintaining mucosal homeostasis during aging. In addition to its effect in oral tolerance induction, it is possible that aging also affects the time length of this phenomenon. According to some authors, oral tolerance is kept for 21 days to 3 months after feeding. Previous studies by our group showed that oral tolerance can be maintained for a period of one and a half year after oral treatment. These contradictory reports can be explained by different experimental protocols that were used. The main difference in the protocols is related to immunization with antigen + adjuvant that is essential to reveal oral tolerance induction. Thus, we also studied the role of inflammatory events triggered by immunization in the oral tolerance induction and maintenance. For that, BALB/c mice at age of 8-12 weeks were treated orally with 20mg of OVA by gavage and immunized with OVA+Al(OH)3 i.p. Primary immunization varied from 7 to 180 days after oral treatment in mice immunized with OVA+Al(OH)3 and a booster was administered 14 days afterwards. Alternatively, primary immunization with OVA+Al(OH)3 was performed 7 days after oral treatment and booster with OVA varied from 14 to 360 days after primary immunization. We observed that only mice primary immunized up to 90 days after oral treatment were able to sustain oral tolerance to all evaluated parameters. However, mice immunized 7 days after oral treatment were able to keep oral tolerance up to one year after oral treatment. These results suggest that immunization with antigen + adjuvant can act strengthening oral tolerance maintenance. The concomitant injection of antigen and adjuvant and the site of immunization were also important for oral tolerance maintenance. In addition, there was an increase in the frequency of Tregs cells CD4+CD25+Foxp3+ and CD4+CD25+LAP+ in DO11.10 OVA transgenic TCR mice after antigen feeding. Moreover, in C57BL/6 and GFP Foxp3+ knockin mice an increase percentage of these could be seem after oral treatment with antigen followed by immunization with OVA+Al(OH)3. When we searched for the possible mechanism by which Al(OH)3 helps in oral tolerance maintenance neither antigen deposits nor uric acid seem to be necessary. We can conclude that many changes in the gut mucosal associated immune system occurs that can be involved in oral tolerance decline in aged mice. In addition, the interval between oral treatment and primary immunization with OVA+Al(OH)3, the concomitant presence of antigen and adjuvant and the site of injection all affect oral tolerance maintenance.